The enigma of ethics: A multidimensional approach - Fraedrich, John (International journal of value-based management, 1991)
The question of what is ethical or unethical has been debated over the centuries with little headway. The purpose of this article is to clarify this problem by presenting three perceptual domains: self, organization, and society, which, when viewed together, explain the problem of determining ethical behavior. Implications of such a perspective are discussed relative to managers facing ethical problems.